1977
DOI: 10.1021/ic50177a008
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of Prussian Blue: Fe4[Fe(CN)6]3.xH2O

Abstract: During this period final calculations were performed and the manuscript was prepared.Registry No. [Te(etu)4]Cl2-2H20, 63848-47-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
676
3
23

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 951 publications
(755 citation statements)
references
References 6 publications
33
676
3
23
Order By: Relevance
“…3.33 for x = 1.0. The water content is found to increase with increasing x for x B 0.8, which is not what is expected and it is contrary to what has been reported in other studies, where alkali-rich compounds have been found to have lower water contents than alkali-free ones [13,14]. The observed variation with x can qualitatively be attributed to the fact that the incorporated K ?…”
Section: Degree Of Hydrationcontrasting
confidence: 96%
See 1 more Smart Citation
“…3.33 for x = 1.0. The water content is found to increase with increasing x for x B 0.8, which is not what is expected and it is contrary to what has been reported in other studies, where alkali-rich compounds have been found to have lower water contents than alkali-free ones [13,14]. The observed variation with x can qualitatively be attributed to the fact that the incorporated K ?…”
Section: Degree Of Hydrationcontrasting
confidence: 96%
“…alkali-free, with formula Fe III [Fe II (CN) 6 ] 3/4 Á3.5-4H 2 O. The two terms soluble and insoluble refer to the ease of peptization rather than true solubility, as both compounds are highly insoluble in water [13,14]. PBAs have a general formula A x M[M 0 (CN) 6 ] z ÁnH 2 O, where M and M 0 are transition metal ions, A is a monovalent cation, and z B 1.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, Mn II -N CMn III/II was selected as the anode to be used in full cells with the Cu II -N C-Fe III/II cathode. X-ray diffraction of the fresh powders of both Cu II -N CFe III and Mn II -N C-Mn III revealed that they both have the FCC Prussian Blue crystal structure 27 . Their fully indexed diffraction spectra are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This structure is composed of a face-centred cubic framework of transition metal cations where each cation is octahedrally coordinated to hexacyanometallate groups ( Fig. 1) [25][26][27] . For instance, in the copper hexacyanoferrate cathode, sixfold carboncoordinated iron and sixfold nitrogen-coordinated copper are linked by CN ligands.…”
mentioning
confidence: 99%
“…Th e previously described Prussian Blue batteries and electrochromics used electrodeposited thin fi lm electrodes that were less than 300 nm thick, and that had mass loadings too low ( μ g cm − 2 ) to be relevant for large-scale energy storage 16 . Th e extreme insolubility of Prussian Blue makes the control of bulk precipitation syntheses diffi cult, and they oft en result in products with poor crystallinity and K + and Fe 3 + impurities 11,12 . Here we replace the nitrogen-coordinated Fe 3 + with Cu 2 + , and use a controlled co-precipitation synthesis to produce highly crystalline nanoparticles of CuHCF with the Prussian Blue open framework structure.…”
mentioning
confidence: 99%